The Determinants of Turnover Intention in the Public Healthcare Sectors Malaysia: A Conceptual Paper - Binti Amer, Noryanne; Abdul Rahim Ridzuan; Sylvia Nabila Azwa Ambad, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study investigates several factors that influence nurses' intentions to depart from their professions in the Malaysian public healthcare system. The research explores the complex interplay of determinants contributing to turnover intention among nurses in the public healthcare sectors. This academic inquiry seeks to contribute deeper understanding of the underlying explanations caused nurse retention in public healthcare sectors in Malaysia. Various factors impact nurse turnover intention in Malaysia, including work-related, personal, and organizational aspects. These factors have been identified in several studies and can impact the retention of nurses in the healthcare industry. Understanding and addressing these factors are crucial for public healthcare sectors to improve nurse retention and provide better quality of care. Hence, the main concern of this research is to examine the association between job demand, work-life balance and turnover intention among nurses in public healthcare sectors. This study contributes to the existing body of knowledge on factors influencing turnover intention among nurses in public healthcare sectors in the context of Malaysian nurses. The findings underscore the need of addressing the causes of work-life balance concerns, such as workload, working hours, and workplace quality, in order to increase nurse retention and, ultimately, nursing care quality. By understanding the relationship between job demand, worklife balance and turnover intention, Malaysian public healthcare sectors can create a favorable work environment to encourage nurse retention and improve patient outcomes.